2020
DOI: 10.1097/sla.0000000000002981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anatomical Resection for Hepatocellular Carcinoma With Microportal Invasion (vp1)

Abstract: Although local recurrence around the resection site was suppressed by AR, AR for HCC with vp1 did not influence the RFS or OS rates after hepatectomy in the modern era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 20 publications
2
51
4
Order By: Relevance
“…Theoretically, the utilization of anatomical resection would hinder dissemination of tumor cells throughout portal venous flow into the remnant liver and would be the surgical technique most apt to reduce early recurrence of HCC following resection. In 2018, Hidaka et al published a retrospective analysis of 546 patients with HCC with microportal invasion (vp1), where they found that local recurrence occurred significantly more frequently in the NAR than the AR group [20]. However, this hypothesis has some limitations in explaining early recurrences as it assumes that tumor cells have not already left the tumor into the portal venous system as tumor circulating cells prior to resection.…”
Section: Theoretical Advantages Of Anatomical Resection Surgical Tmentioning
confidence: 99%
“…Theoretically, the utilization of anatomical resection would hinder dissemination of tumor cells throughout portal venous flow into the remnant liver and would be the surgical technique most apt to reduce early recurrence of HCC following resection. In 2018, Hidaka et al published a retrospective analysis of 546 patients with HCC with microportal invasion (vp1), where they found that local recurrence occurred significantly more frequently in the NAR than the AR group [20]. However, this hypothesis has some limitations in explaining early recurrences as it assumes that tumor cells have not already left the tumor into the portal venous system as tumor circulating cells prior to resection.…”
Section: Theoretical Advantages Of Anatomical Resection Surgical Tmentioning
confidence: 99%
“…When Professor Makuuchi determined the definition of anatomical hepatectomy, he believed that a gross resection of the tumor-bearing liver removes not only the tumor visible to the naked eye but also microvascular invasion that is difficult to detect (30), which has been affirmed by many studies and is also consistent with the findings of our study. Also, some researchers revealed that AR or NAR for HCC with MVI did not influence the recurrence-free survival or OS rates after hepatectomy in the modern era (16).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that anatomical resection (AR) of the liver can be useful in isolating microvascular metastases while removing lesions (14,15). However, multicenter retrospective studies revealed no significant difference between AR and non-anatomical resection (NAR) in terms of tumor-free survival and long-term survival post-operatively (16). In the current study, we aim to establish a valid prediction model to prognose the occurrence of microvascular invasion, and apply this model to compare the efficacy of AR or NAR in the treatment of patients retrospectively.…”
Section: Importance Of Microvascular Invasion Risk and Tumor Size On mentioning
confidence: 99%
“…It has been documented that preoperative blood AFP level, number of tumors, and diameter of tumor are risk factors for predicting prognosis of patients [ 12 , 14 , 22 , 23 ]. Blood AFP level might be positively related to the diameter of tumor in HCC patients, and the presence of tumor enlargement is a predictive factor for poor prognosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%